Calcium/calmodulin-dependent protein kinase II associates with the K+ channel isoform Kv4.3 in adult rat optic nerve - Ogata, Genki; Partida, Gloria J.; Fasoli, Anna; Ishida, Andrew T. (Frontiers in Neuroanatomy, 2022)
Spikes are said to exhibit “memory” in that they can be altered by spikes that precede them. In retinal ganglion cell axons, for example, rapid spiking can slow the propagation of subsequent spikes. This increases inter-spike interval and, thus, low-pass filters instantaneous spike frequency. A K+ ion channel blocker (4-aminopyridine, 4AP) produces similar effects on compound action potentials recorded from optic nerve, and we recently found that reducing autophosphorylation of calcium/calmodulin-dependent protein kinase II (CaMKII) does too. These results would be expected if CaMKII regulates spike propagation by regulating 4AP-sensitive K+ channels. As steps toward identifying a possible substrate, we test whether (i) 4AP alters optic nerve spike shape consistent with reducing K+ current, (ii) 4AP alters spike propagation consistent with effects of reducing CaMKII activation, (iii) antibodies directed against 4AP-sensitive and CaMKII-regulated K+ channels bind to optic nerve axons, and (iv) optic nerve CaMKII co-immunoprecipitates with 4AP-sensitive K+ channels. We find that, in adult rat optic nerve, (i) 4AP selectively slows spike repolarization, (ii) 4AP slows spike propagation, (iii) immunogen-blockable staining is achieved with anti-Kv4.3 antibodies but not with antibodies directed against Kv1.4 or Kv4.2, and (iv) CaMKII associates with Kv4.3. This identifies a substrate that may underlie activity-dependent spike regulation in adult visual system pathways.